Gene transfection of human mesenchymal stem cells with a nano‐hydroxyapatite–collagen scaffold containing DNA‐functionalized calcium phosphate nanoparticles. (30th May 2016) - Tenkumo, Taichi; Vanegas Sáenz, Juan Ramón; Takada, Yukyo; Takahashi, Masatoshi; Rotan, Olga; Sokolova, Viktoriya; Epple, Matthias; Sasaki, Keiichi
Abstract : This study aimed to fabricate a growth factor‐releasing biodegradable scaffold for tissue regeneration. We prepared multishell calcium phosphate (CaP) nanoparticles functionalized with DNA, polyethyleneimine (PEI), protamine and octa‐arginine (R8) and compared their respective transfection activity and cell viability measures using human mesenchymal stem cells. DNA–protamine complexes improved the transfection efficiency of CaP nanoparticles with the exception of those functionalized with R8. These complexes also greatly reduced the cytotoxicity of PEI. In addition, we also fabricated DNA–protamine‐functionalized CaP nanoparticle‐loaded nano‐hydroxyapatite–collagen scaffolds and investigated their gene transfection efficiencies. These experiments showed that the scaffolds were associated with moderate hMSC cell viability and were capable of releasing the BMP‐2 protein into hMSCs following gene transfection. In particular, the scaffold loaded with protamine‐containing CaP nanoparticles showed the highest cell viability and transfection efficiency in hMSCs; thus, it might be suitable to serve as an efficient growth factor‐releasing scaffold. Abstract : We developed a successful growth factor release system from a scaffold.